Pengaruh Ketahanan Pangan terhadap Rata-Rata Pengeluaran Masyarakat di Jawa Tengah - Anandhiya Anandhiya; Agus Arifin; Istiqomah Istiqomah (Universitas Batanghari Jambi, 2021)
Food security is included in the second Sustainable Development Goals (SDGs), namely to overcome poverty, improve quality of life and regional development. This study aims to analyze the effect of population, income per capita, rice production and poverty on the average per capita expenditure in Central Java Province in 2015-2019. The research method uses multiple linear regression with the penel data model. The results showed that the population and rice production had a significant effect on the average per capita expenditure in Central Java Province in 2015-2019. Meanwhile, income per capita and poverty not significant effect on average per capita expenditure in Central Java Province in 2015-2019.. The implication of government policy is to maintain food security in Indonesia and be able to reduce the population by streamlining the family planning program.